Optimum laser parameters for 1D radiation pressure acceleration. (30th April 2015) - Schmidt, Peter; Boine-Frankenheim, Oliver; Mulser, Peter
Abstract Laser ion acceleration (Wilks et al., 2001; Passoni et al., 2010) has become an interesting field of research in the past years. Several experiments, such as LIGHT (Schollmeier et al., 2008; Bagnoud et al., 2010; Busold et al., 2013; 2014a; 2014b) are performed worldwide. High intense, pulsed laser beams are used to generate and accelerate a plasma. For higher laser intensities (>1021 W cm−1), simulations (Esirkepov et al., 2004; Macchi et al., 2005; 2009; 2010; Robinson et al., 2008; Rykovanov et al., 2008; Henig et al., 2009; Schlegel et al., 2009; Shoucri et al., 2011; 2013; 2014; Kar et al., 2012; Korzhimanov et al., 2012; Shoucri, 2012) have revealed a new acceleration mechanism: The Radiation Pressure Acceleration. The entire foil target is accelerated by the radiation pressure of the laser pulse. Ideally, a sharp peak spectrum is generated, with energies up to GeV and nearly solid body density. This work faces on a detailed analysis of the acceleration mechanism in order to develop the optimum laser- and target parameters for the process. The analysis is supported by one-dimensional PIC simulations, using the commercial code VSim© Tech-X (2015).